THE MAIN CONTENT OF THE MILITARY-PATRIOTIC EDUCATION (Archive of Conferences, 2021)
this article analyzes the military-patriotic education of youth and its goals and objectives. The process of patriotic education plays a leading role, has a great influence on the formation of the future defender of the Fatherland, since the content of educational disciplines reflects important spiritual, moral, cultural traditions of our people. But this process is not enough to limit itself to individual components of patriotic education. He must be ready to defend the Motherland, provide comprehensive active practical influence on the state of all its components and promote awareness this readiness as the most important aspect of the life of young people